Why be happy when you could be normal? - Winterson, Jeanette 1959- (New York Grove Press, 2011)
This memoir is a tough-minded search for belonging, for love, an identity, a home, and a mother by the author of "Oranges Are Not the Only Fruit"--winner of the Whitbread First Novel award and the inspiration behind the award-winning BBC television adaptation "Oranges."
The wrong crib -- My advice to anybody is : get born -- In the beginning was the word -- The trouble with a book... -- At home -- Church -- Accrington -- The apocalypse -- English literature A-Z -- This is the road -- Art and lies -- Intermission -- The night sea voyage -- This appointment takes place in the past -- Strange meeting -- The wound -- Coda.
Keywords: Winterson, Jeanette -- 1959-.; Lesbians -- England -- Biography; Authors, English -- Biography; Mothers and daughters -- Biography